Dermal Filler Presenting as Lobular Radiopacities in an Edentulous Patient: A Clinical Report. Issue 8 (20th September 2017) - Koka, Sreenivas; Shah, Kumar; Mallya, Sanjay
Abstract: This clinical report describes the unusual appearance of radiopacities, lobular in nature, observed on a dental panoramic image of an edentulous patient. Upon questioning, the patient described a history of recently having hydroxylapatite‐based dermal filler placed in her right and left cheeks to reduce wrinkles and enhance cosmetic appearance. The localization and shape of the radiopacities were consistent with the placement of the dermal filler.